Canthal Rotation Flap: Analysis of Flap Mechanics. Issue 1 (January 2021) - Syed, Zain U.; Madden, Nichelle; Donnelly, Heidi B.
Abstract : BACKGROUND: Surgical defects of the medial canthus lack reconstructive options that are reproducible, precise, and uncomplicated. The canthal rotation flap is a simple rotation flap that respects the geometry of this anatomic location. OBJECTIVE: To describe the authors' experience with reconstructive planning, flap mechanics, and geometric analysis of the medial canthus to achieve the best cosmetic outcome when using the canthal rotation flap. METHODS: A retrospective review of 16 cases performed at Dayton Skin Care Specialists and Skin Care Specialty Physicians between 2016 and 2018 was completed with a blinded visual analog score (VAS). RESULTS: Sixteen patients with Mohs defects in the medial canthus were reconstructed using the canthal rotation flap. Defect diameters ranged from 0.8 to 2.7 cm. Patient ages ranged from 17 to 88 years. The mean flap dimensions were 4.8 cm by 2.15 cm. No major complications were noted. The VAS scar rating at 2 to 5 months follow-up was available for 10 of 16 patients; the mean VAS was 2.1. CONCLUSION: The canthal rotation flap is a reliable, single stage repair for small defects of the medial canthus that is optimized for the unique geometry of the medial canthus. This repair technique adds to the paucity of reconstructive options for the medial canthus. Abstract : Supplemental Digital Content is Available in the Text.